Efforts To Achieve Sustainable Development In The Preparation Of Women's Empowerment Policies In Equitable Economic Activities - Putri, Citraresmi Widoretno; Wijaya, Satria Yudha (Universitas Muhammadiyah Sumatera Utara, 2024)
Strengthening women's economy is a good synergy and collaboration of the legislature, executive and community groups. With support for gender equality issues, women can maximize their potential, so that they can become pillars of national economic recovery. The problem is how to implement sustainable development with a gender perspective and how to realize women's empowerment policies in equitable economic activities. The type of research used is normative-empirical juridical. The results are that in the implementation of sustainable development with a gender perspective, there has been inequality that has befallen women. In several aspects of development, women are always the disadvantaged party. In fact, with gender equality, this is relevant to economic growth, because women who think they can support life, both their own lives and their families, will increase their consumption activities which will also affect the level of economic growth. Furthermore, efforts to realize women's empowerment policies in equitable economic activities have been carried out by the Government through several efforts by emphasizing four main sectors, namely in the fields of education, health, employment, and related to the prevention of violence. One of them is in the field of employment, the government focuses on expanding employment opportunities, encouraging labor market gaps, adjusting salaries to market mechanisms, improving workforce skills and capacity with training for women, and strengthening the implementation of labor policies that accommodate gender equality.